2010
DOI: 10.1186/1476-511x-9-131
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combination therapy of allicin and fenofibrate on high fat diet-induced vascular endothelium dysfunction and liver damage in rats

Abstract: BackgroundIt is designed to investigate the effects of combination therapy of allicin and fenofibrate on the endothelial and liver functions in rats with hyperlipidemia.MethodsThe healthy male Wistar rats fed high fat diet were treated with fenofibrate (80 mg/kg per day) alone, allicin (60 mg/kg per day) alone and a lower dasage of combined therapy (allicin 20 mg/kg per day and fenofibrate 30 mg/kg per day) respectively for 8 weeks. The serum levels of cholesterol, triglyceride, nitrogen oxidative, alanine tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 25 publications
3
27
0
1
Order By: Relevance
“…In this study Fenofibrate did not reduce serum LDL of rats fed with atherogenic diet and this is in contrast with the study of Li et al, (2010) who found that hyperlipidemic rats treated with a high dose of Fenofibrate of 80mg/kg/day for 12 weeks reduced serum TG ,TC and LDL significantly. This indicates that the beneficial effects of Fenofibrate on serum LDL probably needs more time and higher doses would have been more informative in our study (37). Serum transaminases (ALT, AST) in this study, increased significantly in hyperlipidemic rats treated with TGS of both concentrations (0.50% and 0.75% w/w).…”
Section: Comparison Of Tgs Effects On Liver Enzymes With Rosuvastatinmentioning
confidence: 46%
See 1 more Smart Citation
“…In this study Fenofibrate did not reduce serum LDL of rats fed with atherogenic diet and this is in contrast with the study of Li et al, (2010) who found that hyperlipidemic rats treated with a high dose of Fenofibrate of 80mg/kg/day for 12 weeks reduced serum TG ,TC and LDL significantly. This indicates that the beneficial effects of Fenofibrate on serum LDL probably needs more time and higher doses would have been more informative in our study (37). Serum transaminases (ALT, AST) in this study, increased significantly in hyperlipidemic rats treated with TGS of both concentrations (0.50% and 0.75% w/w).…”
Section: Comparison Of Tgs Effects On Liver Enzymes With Rosuvastatinmentioning
confidence: 46%
“…It has been reported that Fenofibrate activates the aminotransferase gene expression, thus leading to a mild and transient elevation of aminotransferase via PPAR? through mechanisms involving increased levels of reactive oxygen species and intracellular glutathion depletion, thus leading to mitochondrial dysfunction and a perturbation of intracellular Ca++ homeostasis and also cell death (41); (37).…”
Section: Comparison Of Tgs Effects On Liver Enzymes With Rosuvastatinmentioning
confidence: 99%
“…Previous studies have documented that nutritional application of various metabolic dysfunction have been conducted with the aim of regulating obesity [13-16]. There is a developing interest in the use of phytochemical compounds as medicinal alternative due to their lack of toxicity and the relative ease and cost of production.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that allicin protects cells against oxidative stress by inducing the generation of antioxidant products [13]. Allicin altered the fatty acid levels of rats fed high-fat diets [14]. Recently, several studies have demonstrated that allicin decreases cholesterol and blood pressure [10, 15].…”
Section: Introductionmentioning
confidence: 99%